The Need for a System Science Approach to Global Magnetospheric Models - Delzanno, Gian Luca; Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2022)
This perspective advocates for the need of a combined system science approach to global magnetospheric models and to spacecraft magnetospheric data to answer the question ‘Do simulations behave in the same manner as the magnetosphere does?’ (instead of the standard validation question ‘How well do simulations reproduce spacecraft data?’). This approach will (1) validate global magnetospheric models statistically, without the need for a direct comparison against spacecraft data, (2) expose the deficiencies of the models, and (3) provide physics support to the system analysis performed on the magnetospheric system.